A rare case of Acute Motor and Sensory Axonal Neuropathy (AMSAN) and Immune Thrombocytopenic Purpura (ITP) related to Hemophilus influenzae - Satyasi, Vivek; Ahmed, Aiesha; Farheen, Amtul (RRNMF Neuromuscular Journal, 2021)
We describe a rare case presenting with both signs of acute motor and sensory axonal neuropathy (AMSAN) and immune thrombocytopenic purpura (ITP) possibly triggered by Hemophilus influenzae. Guillain-Barre is an autoimmune disorder purported to be due to molecular mimicry, often with a preceding infection, leading to myelin sheath or even axonal damage, AMSAN, in the peripheral nervous system (PNS). Rarely, there have been case reports of concurrent acute autoimmune disorders leading to a more complex presentation and additional comorbidities. A 42-year-old man presented with 2 days of progressive lower and upper extremity paresthesia’s, ataxia preceded by an upper respiratory infection. Examination showed areflexia and purpura, recent oral mucosal hemorrhage. Lab results showed severe thrombocytopenia suspicious for ITP. Over the ensuing weeks while inpatient, his condition quickly deteriorated to requiring an intubation for respiratory failure and not immediately responsive to IVIG. Recovery, both for AMSAN confirmed by EMG and ITP, was eventually achieved with time and five treatments of plasmapheresis and eventually was discharged to a rehabilitation facility. A thorough infectious workup revealed a possible trigger being Haemophilus influenzae. There have been rare occasions of concurrent GBS and ITP, but even more rare is the presence of both AMSAN and ITP which requires quick recognition and evaluation. This case highlights the need for a thorough initial history taking and a general physical exam, in addition to unique management decisions and strategies in patients with suspected GBS as there may be signs of other associated disorders that require immediate attention.